The Current Big Thing is Really Small – A Review on Nanomaterials in Medicine with an Overview of Metal Oxide Nanomaterial Toxicity - Gandham, A Priyadarshini; Sweeya, Pisupati SR; Karra, Geetha; Chidrawar, Dr. Vijay R; Rao, Dr. V. Uma Maheswara (Asian Journal of Pharmaceutical Research and Development, 2013)
Nanotechnology is being employed in the pharmaceutical field for many reasons, but perhaps the leading goals are to improve drug solubility/bio-availability and/or delivery to various sites of action and development of advanced diagnostic and therapeutic devices. Among various nanomaterials, metal oxide nanomaterials have a promising application in nanomedicine. In recent years, the health impacts of nanomaterials and ultrafine particles have been paid attention. Due to a wide range of differences between the properties of nanomaterials among them and when compared to their bulk forms, there is a need to study both acute and chronic toxicities of these nanomaterials to assess their health impacts and toxicities in humans. In this review, application of nanomaterials in nano-medicine, toxicities of metal oxide nanomaterials and challenges before nano-drugs in pharmaceutical industry have been given an overview.